DEVELOPMENT OF STUDENTS' CREATIVE THINKING COMPETENCIES THROUGH DIGITAL PLATFORMS AND ONLINE INTERACTIVE GAME SERVICES (Journal of Uzbekistan’s Development and Research, 2025)
This article discusses digital platforms widely used in modern education, the capabilities of digital platforms, and the functions of online interactive gaming services in education.